Gut Microbiota Dysbiosis Accelerates Prostate Cancer Progression Through Increased LPCAT1 Expression and Enhanced DNA Repair Pathways - Liu, Yufei; Yang, Chen; Zhang, Zheyu; Jiang, Haowen (Frontiers in Oncology, 2021)
Gut microbiota dysbiosis is related to cancer development and progression. Our previous study showed that Ruminococcus was more abundant in CRPC (Castration-resistant prostate cancer) than HSPC (Hormone-sensitive prostate cancer) individuals. Here, we determined the potential mechanism of microbiota dysbiosis in prostate cancer (PCa) progression. Metagenomics was used to verify the gut microbial discrepancies between CRPC and HSPC individuals. Fecal microbiota transplantation (FMT) was performed by transferring the fecal suspension of CRPC or HSPC individuals to TRAMP mice. Afterwards, the mice’s prostate histopathology and gut microbiota composition were determined. Since Ruminococcus was demonstrated to correlate with phospholipid metabolism, we used lipidomics to examine the mice’s fecal lipid profiles. The expression of LPCAT1 the key enzyme for phospholipid remodeling in mice prostate was also examined. Meanwhile, both microbial functions prediction and LPCAT1 GSEA analysis (Gene Set Enrichment Analysis) indicated DNA repair pathways, we further determined the expressions of RAD51 and DNA-PKcs in mice prostate. The results showed that gut Ruminococcus was significantly more abundant in CRPC individuals. FMT using CRPC feces accelerated mice’s PCa progression and increased their gut Ruminococcus abundance. Majority of fecal lipids including lysophosphatidylcholine and phosphatidylcholine were upregulated in CRPC FMT treated mice, accompanied with enhanced expressions of LPCAT1, RAD51, and DNA-PKcs in mice prostate. We reported an abundant colonization of Ruminococcus in the gut of CRPC individuals and mice receiving their fecal suspensions, and revealed the promotive capability of Ruminococcus in PCa progression via upregulating LPCAT1 and DNA repair protein expressions. The bacterium and its downstream pathways may become the targets of therapies for PCa in the future.